Comparative assessment of high-risk cardiovascular medication knowledge between practising and student nurses: a descriptive multi-centre study - Najla Taslim; Amal Turikham Alghamdi; Dana Ali Alqarni; Shaista Rashid; Dustin Todd Edge (Medicinski glasnik, 2023)
Aim: To examine unexplored knowledge of cardiovascular highrisk medications and perception thereof among practising nurses and students in the Kingdom of Saudi Arabia (KSA). Methods: The multicentre cross-sectional quantitative study used an online survey dichotomised into a knowledge test (true/false and multiple choice questions) and a perception assessment (closed-ended questions). Four hundred and eighteen nurses participated in the study. Results: In the knowledge test, 19 (4.5%) participants scored high (?71%), while 83 (19.8%) and 316 (75.5%) demonstrated moderate (score ?51-70%) and poor performance (score ?50%), respectively. In a comparative analysis, the knowledge level of staff nurses was significantly higher than the students but not the other nurses’ cohort. Nurses' specialty and region of KSA were strongly associated with the knowledge level. Emergency room nurses and those belonging to the eastern region of KSA exhibited higher knowledge levels than other subgroups. A vast majority of nurses, 128 (30.6 %), rated their knowledge of medicines as somewhat sufficient, while quoting insufficient knowledge 226 (54.1%) as the major cause of medication errors. Three hundred and sixteen (75%) nurses expressed interest in undergoing specialised training in high-alert medication-based therapy preferably in a classroom setting by 279 (66.7%). Conclusion: This study revealed a marked knowledge deficit in high-risk cardiovascular drugs among nurses. The pharmacological curriculum in nursing schools should be tailored to be clinically oriented and reinforced with problem-based learning. Continued pharmacology education focusing on high-risk drugs should be implemented among nurses to safeguard patient lives by mitigating the risks of medication error.
Keywords: cardiovascular drugs; curriculum; Kingdom of Saudi Arabia; nurses knowledge; nursing students